Survival Rate and Growth of Pterapogon kauderni Larvae Given Different Feed Types - Safir, Muhammad; Tobigo, Desiana Trisnawati; Mangitung, Septina F; Sambaeni, Daniel; Ryaldi, Muhammad; Adam, Rizilvana Datu; Zainab, Zainab; Husain, Husain (FAPETKAN UNTAD, 2020)
This research was conducted to determine the type of feed that provides high survival and growth in Pterapogon kauderni larvae after release from the mother's mouth. The study was designed using three treatments including; commercial feeding (A), shrimp/Acetes (B), and rotifer/Rotifera sp. (C). Each treatment was given three replications. Feed is given three times a day (morning, afternoon and evening) by at-satiation. Maintenance time is carried out for one week. The analysis showed that the highest daily growth rate occurred in treatment B (1.39 Â± 0.92%), and was significantly different (P <0.05) with treatment A (0.90 Â± 0.02%). The highest increase in biomass occurred in treatment C (0.005 g) compared to other treatments (A = 0.003 g, B = 0.003 g). Survival for all treatments did not differ significantly (P> 0.05). In conclusion, the type of feed that provides the highest survival and growth in P. kauderni larvae after release from the mother's mouth is rotifers.